2001
DOI: 10.1182/blood.v98.10.3058
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tumor necrosis factor–related apoptosis-inducing ligand, Apo2L, and its receptors in myelodysplastic syndrome: effects on in vitro hemopoiesis

Abstract: Tumor necrosis factor-related apoptosisinducing ligand (TRAIL), a member of the tumor necrosis factor (TNF) family, binds to several cell-surface receptors with distinct functions (agonistic receptors 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 34 publications
6
94
1
3
Order By: Relevance
“…[2][3][4][5][6] Several apoptosis-inducing ligand/ receptor pathways have been identified 1,[7][8][9] and have been shown to be upregulated in MDS marrow. 4,[10][11][12][13] FAS ligand (FAS-L) and tumor necrosis factor-alpha (TNF-a) induce apoptosis by binding to their natural receptors FAS (CD95/Apo-1) and TNF receptors 1 (TNFR1) and 2 (TNFR2), respectively. 7,8 The TNF-related apoptosis-inducing ligand (TRAIL) also initiates apoptosis through binding to death receptors DR4 (TRAIL receptor 1) and DR5 (TRAIL receptor 2); however, nonagonistic (decoy) receptors (TRAIL receptors 3 and 4) compete for TRAIL binding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] Several apoptosis-inducing ligand/ receptor pathways have been identified 1,[7][8][9] and have been shown to be upregulated in MDS marrow. 4,[10][11][12][13] FAS ligand (FAS-L) and tumor necrosis factor-alpha (TNF-a) induce apoptosis by binding to their natural receptors FAS (CD95/Apo-1) and TNF receptors 1 (TNFR1) and 2 (TNFR2), respectively. 7,8 The TNF-related apoptosis-inducing ligand (TRAIL) also initiates apoptosis through binding to death receptors DR4 (TRAIL receptor 1) and DR5 (TRAIL receptor 2); however, nonagonistic (decoy) receptors (TRAIL receptors 3 and 4) compete for TRAIL binding.…”
Section: Introductionmentioning
confidence: 99%
“…7,9 We have previously shown that the ratio of agonistic to decoy receptors in MDS marrow is upregulated in comparison to marrow from normal donors. 13 Such a pattern would favor the occurrence of apoptosis in MDS cells relative to normal marrow cells. However, in MDS marrow, apoptosis occurs in normal as well as in clonal precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Messages encoding DR4 and DR5, as well as TRAIL itself, have been detected in normal myeloid progenitors by RT-PCR. 96,97 Despite the expression of TRAIL receptors, exogenous TRAIL has little effect on myeloid progenitors from normal marrow, [96][97][98] again reinforcing the complexity of signaling through this pathway.…”
Section: Molecular Determinants Of Trail Sensitivitymentioning
confidence: 99%
“…Deeg and co-workers reported increased expression of TRAIL and its receptors in marrow from patients with both early and late MDS. 96 In samples from early MDS, TRAIL induced depletion of cytogenetically abnormal myeloid progenitor colonies and enhanced growth of normal myeloid progenitors in vitro. 96 In samples from more advanced MDS (RAEB-T and t-AML), TRAIL treatment in vitro caused a statistically significant decrease in the number of abnormal myeloid progenitors.…”
Section: Molecular Determinants Of Trail Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation